The vulnerary potential of botanical medicines in the treatment of bacterial pathologies in fish - Nurzhanova, F.; Absatirov, G.; Sidikhov, B.; Sidorchuk, A.; Ginayatov, N.; Murzabaev, K. (VETERINARY WORLD, 2021)
Background and Aim: The use of plant-based medicine in treating and preventing fish disease has become increasingly popular due to the resistance of bacterial pathogens to chemicals widely used in aquaculture. This study explored the vulnerary - effect of botanical medicines made from local raw materials (greater celandine [Chelidonium majus L.], St. John's wort [Hypericum perforatum L.], and bur beggar-ticks [Bidens tripartita L.]) in the treatment of sturgeon bacterial pathologies in a controlled environment.Наблюдался положительный лечебный эффект C. majus , H. perforatum и B. tripartita , что согласуется с использованием этих растений в народной и традиционной медицине. Растительные материалы устраняли инфекцию, обладали противовоспалительным и противовоспалительным действием, стимулировали развитие грануляционной ткани и улучшали регенерацию. По сравнению с широко распространенными методами (антибиотики и другие химиотерапевтические средства), ботаническая медицина способствовала более эффективному лечению за тот же период без побочных эффектов.
Keywords: импакт-фактор 2021; научный журнал; периодическое издание; дальнее зарубежье; зарубежное издание; скопус; кларивате аналитикс; растительное сырье; томсон; заживление раны; рыба; зарубежные авторы